2022
DOI: 10.1007/s10461-022-03697-3
|View full text |Cite
|
Sign up to set email alerts
|

Posttraumatic Growth and Posttraumatic Stress Symptoms in People with HIV

Abstract: Receiving a diagnosis of HIV can be challenging. People with HIV (PWH) can experience high levels of distress, as well as some positive psychological changes associated with post-traumatic growth. However, the mechanisms which underlying the association of a highly stressful event (i.e., being diagnosed with HIV) and posttraumatic growth (PTG) and posttraumatic stress symptoms (PTSS) are under-explored, and this is the focus of the study. Cross-sectional survey data were provided by 77 PWH living in New Zealan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
4
0
2
Order By: Relevance
“…A high level of adherence is necessary for successful treatment with ART [ 9 ]. This corresponds with agreed recommendations, shared decision-making, patients’ perception, and experiences from the Health-Care Professionals (HCPs) as cornerstones for ART adherence [ 10 ]. Despite the decreasing fear of AIDS and the paradigm change by the reduction of old clichés, PLWH are still confronted with discrimination and stigmatization in different areas of life [ 11 ].…”
Section: Introductionmentioning
confidence: 54%
“…A high level of adherence is necessary for successful treatment with ART [ 9 ]. This corresponds with agreed recommendations, shared decision-making, patients’ perception, and experiences from the Health-Care Professionals (HCPs) as cornerstones for ART adherence [ 10 ]. Despite the decreasing fear of AIDS and the paradigm change by the reduction of old clichés, PLWH are still confronted with discrimination and stigmatization in different areas of life [ 11 ].…”
Section: Introductionmentioning
confidence: 54%
“…Unfortunately, they did not include self-blame as a coping strategy but typically venting and mental disengagement are assigned to the same avoidance coping category as self-blame. Chi et al (2022) found that deliberate rumination was positively associated with avoidance coping in people with HIV. Existing studies indicate mixed findings about relations between types of rumination and coping strategies, giving more attention to deliberate than intrusive rumination.…”
Section: Introductionmentioning
confidence: 95%
“…Changes can be experienced in the view of the self, relationships with others, and/or worldview and philosophy of life ( Tedeschi and Calhoun, 1995 ; Tedeschi et al, 2018 ). Studies investigate PTG in various trauma survivors such as war veterans ( Maguen et al, 2011 ), terminal illnesses ( Chi et al, 2022 ), natural disasters ( Jia et al, 2017 ), and accident survivors ( Nishi et al, 2010 ), however, some traumatic experiences such as IPV still receive less attention ( Elderton et al, 2017 ). The dynamics of IPV make it hard to apply the knowledge about PTG from other traumatic contexts.…”
Section: Introductionmentioning
confidence: 99%
“…Regarding associations with coping, few studies provide information on correlative associations between event centrality and several individual coping strategies. These report positive correlations between event centrality and problem-focused coping, emotion-focused coping, avoidant coping, and active coping (Boals & Schuettler, 2011; Chi et al, 2022).…”
Section: Dyadic Coping and Chronic Illnessmentioning
confidence: 99%